A Rabbit Model for Prolonged Continuous Intravenous Infusion Via a Peripherally Inserted Central Catheter - Dor, Eyal; David, Tseela; Dekel Jaoui, Hani; Schwartz, Arieh; Baruchi, Tzadok; Torgeman, Amram; Ben David, Alon; Rosen, Osnat; Tal, Arnon; Rosner, Amir; Zichel, Ran; Diamant, Eran (Frontiers in Pharmacology, 2021)
Medical treatment may require the continuous intravenous (IV) infusion of drugs to sustain the therapeutic blood concentration and to minimize dosing errors. Animal disease models that ultimately mimic the intended use of new potential drugs via a continuous IV infusion in unrestrained, free roaming animals are required. While peripherally inserted central catheters (PICCs) and other central line techniques for prolonged IV infusion of drugs are prevalent in the clinic, continuous IV infusion methods in an animal model are challenging and limited. In most cases, continuous IV infusion methods require surgical knowledge as well as expensive and complicated equipment. In the current work, we established a novel rabbit model for prolonged continuous IV infusion by inserting a PICC line from the marginal ear vein to the superior vena cava and connecting it to an externally carried ambulatory infusion pump. Either saline or a clinically relevant formulation could be steadily and continuously infused at 3–6 ml/hour for 11 consecutive days into freely moving rabbits while maintaining normal body temperature, weight, and respiration physiology, as determined by daily spirometry. This new model is simple to execute and can advance the ability to administer and test new drug candidates.